Specific Features of Students’ Adaptation to The Distance Learning Process - Nozimov Jakhongir Tokhirovich (Indonesian Journal Publisher, 2025)
This article explores the specific psychological, social, and academic features of students’ adaptation to the distance learning process. As online education becomes an integral part of global education systems particularly after the COVID-19 pandemic understanding how students adjust to virtual learning environments has gained significant academic attention. The research focuses on both internal and external factors that influence a student’s ability to adapt successfully. These factors include self-motivation, emotional resilience, self-discipline, time management skills, digital literacy, and the quality of interpersonal communication in the virtual classroom. The article examines the psychological aspects of distance learning, such as the challenges of maintaining focus and emotional balance in the absence of physical interaction. It also discusses the impact of social dynamics, including peer collaboration and instructor engagement, on students’ feelings of inclusion and academic motivation. Moreover, the academic and technical dimensions of adaptation are reviewed, emphasizing the importance of technological infrastructure, access to digital resources, and well-designed online learning platforms